2022
DOI: 10.4236/ijg.2022.139040
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical Triggers as a Cause of Strong Earthquakes

Abstract: The planetary geometries were studied at the moments of 92 strong earthquakes with a magnitude of more than 8 on the Richter scale (R8+) for the period from 1900 to 2011. Three main planetary schemes were specified, namely the schemes of the generalized Archimedes lever (gAL) and the Kepler conjunction (gKc), as well as a new geometry of the triangles of the remote signal catcher (cRS). It was discovered 22 gAL, 42 gKc and 28 cRS geometries, which are 23.9%, 45.7%, and 30.4%, respectively, from the total 92 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…To calculate each planet/sun alignment, we took advantage of the Astropy package in python (The Astropy Collaboration et al, 2018, 2022 that allows us to calculate the position of any planets in the solar system, the Sun, and the moon at any time. For each day covering the period of the earthquake catalog, we calculated if there was a conjunction or not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate each planet/sun alignment, we took advantage of the Astropy package in python (The Astropy Collaboration et al, 2018, 2022 that allows us to calculate the position of any planets in the solar system, the Sun, and the moon at any time. For each day covering the period of the earthquake catalog, we calculated if there was a conjunction or not.…”
Section: Methodsmentioning
confidence: 99%
“…By making a large number of predictions (Garcia, 2017;Service Checknews, 2019), some of them may come true, but that does not mean that the method has any predictive power. The only literature available arguing that conjunctions can be used to predict earthquake occurrence either calls into question fundamental physics without any proof (Omerbashich, 2011;Safronov, 2022), or does not show the background rate of conjunctions (Awadh, 2021). The major logical flaw in these analyses is showing only events that are associated with conjunctions while not paying attention to the total quantity of conjunctions (see Khalisi, 2021;Zanette, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of attempts have been made to explain the influence of planetary [45], and the references given in them. However, in this study, as well as in the previous ones [3] and [39], the author assumes that the cause of these phenomena is of an inertial-gravitational nature, that is, it goes beyond the general theory of relativity. The main opponents of these studies are supporters of Albert Einstein's theory.…”
Section: Introductionmentioning
confidence: 91%
“…The purpose of this study is once again to test the relationship between the planetary geometry and strong earthquakes. Thus, this work, as well as the author's previous studies [1] [2] and [3], are not original since they represent a reworking Open Journal of Earthquake Research of the knowledge of the great ancient philosophers, astronomers and mathematicians, such as Pythagoras, Philolaus, Eudoxus, Plato, Archimedes, Aristotle, Hypatia and many others.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of this study with previous works is shown in Figure 1. This scheme demonstrates severe, moderate and minor impacts on the Earth, which were studied early in [14] [15] [16] [17]. In [14], the basic principles of creating habitable planets around stars in the Milky Way Galaxy were developed.…”
Section: Introductionmentioning
confidence: 99%